Hierarchical tendencies and functional patterns among Mainland China's megaregions. Issue 2 (4th March 2017) - Duan, Xuejun; Derudder, Ben; Ye, Lei; Shen, Wei
Abstract: This paper presents an empirical analysis of hierarchical tendencies and functional patterns in the development of Mainland China's space-economy by operationalizing the concept of "megaregions." Drawing on the burgeoning literature on megaregions, we first argue that under conditions of economic globalization the megaregion concept does indeed present an effective tool to study the spatial agglomeration of the key components of China's economic development. Second, we analyze the development status and the key functional characteristics of 16 prospective Chinese megaregions by constructing an index system consisting of 5 functions and 36 indicators. Third, we calculate an entropy index to rank megaregions according to their overall development status and reveal functional differences by applying cluster analysis. We find that the Yangtze River Delta, Beijing–Tianjin–Hebei Metropolitan Area, and the Pearl River Delta stand out, identify different varieties of megaregions according to their dominant functional characteristics, and explore the main policy dimensions of the persistent west–east divides observed. The paper is concluded with a discussion of potential avenues for future research.